Contemporary Issues Within Caribbean Economies - Cannonier, Colin; Galloway Burke, Monica (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Contemporary Issues within Caribbean Economies offers an exceptional blend of practical policy making experience and fresh academic insight to the economic challenges faced by the region. A must read for all who are passionate about changing the region's development trajectory, the authors discuss sources of inflows such as tourism, foreign direct investment, and remittances, highlighting their significance as well as susceptibility to sudden stops. The volume is also very timely - current issues such as debt, employment, health, and technology receive prominence, but importantly it provides forward insight into how the region should adapt to the impact of the Covid-19 pandemic." - Dr. Hyginus 'Gene' Leon, President, Caribbean Development Bank and former Advisor, International Monetary Fund The Caribbean economy remains a region with many paradoxes. Despite a relative abundance of natural and valuable resources, including its people, large segments of the region still grapple with, inter alia, unsustainable debt levels, environmental degradation, high unemployment, climate change, limited technological innovation, soaring energy costs, remittance and tourism dependency, adverse exchange rates, noncommunicable diseases, and domestic politics. The poorest countries remain more vulnerable to external factors related to trade and global financial sector issues. This edited volume takes a closer look at the contemporary issues related to the economies of the Caribbean. The book provides an added dimension in that each of the chapters includes the contributions of a scholar with lived experiences in and knowledge of the region. Indeed, the book underscores the detailed evidence-based research and perspectives on topics providing insights into the current landscape of the Caribbean. Ultimately, understanding the Caribbean in its varied contexts is an important milestone in pursuing policies that will contribute to flourishing economies replete with sustained growth and development. Dr. Colin Cannonier is an Associate Professor of Economics at Belmont University and fellow at the Global Labor Organization. He was a first-class cricketer and economist at the Eastern Caribbean Central Bank. Dr. Monica Galloway Burke is a Professor in the Department of Counseling and Student Affairs at Western Kentucky University.
Chapter 1. Introduction (Monica Galloway Burke and Colin Cannonier) -- Chapter 2. Debt Burden in Small Island Caribbean States and Prospects for Debt Relief (Dillon Alleyne and Machel Pantin) -- Chapter 3. Technology, Growth and Productivity in the Caribbean (Wendell Samuel) -- Chapter 4. Estimating the Economic Costs of Noncommunicable Diseases in CARICOM (Samuel Braithwaite) -- Chapter 5. Taxes and Fiscal Sustainability in Caribbean Countries (Jeetendra Khadan and Inder Ruprah) -- Chapter 6. Employment and Earnings Disparity: A Comparison of "Belongers" and "Non-Belongers" in the Turks and Caicos Islands (Amos C. Peters) -- Chapter 7. Exchange Rate and Inflation Dynamics, and Monetary Policy in Haiti (Yves Nithder Pierre) -- Chapter 8. The Impact of Remittances on the Real Exchange Rate: Evidence from Haiti (Carl-Henri Prophète and Dudley Augustin) -- Chapter 9. Remittances and Financial Development in Caribbean Countries (Colin Cannonier and Marcus Bansah) -- Chapter 10. Caribbean Tourism Development, Sustainability, and Impacts (David Mc. Arthur Baker) -- Chapter 11. The Role of the Bahamas Government in Tourism (Madlyn M. Bonimy).
Keywords: Latin America-Economic conditions; Economic policy; Economic development; Tourism; Development economics; Latin American/Caribbean Economics; Economic Policy; Economic Growth; Tourism Economics; Development Economics